2000
DOI: 10.1592/phco.20.4.292.34883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Drug‐Induced Thrombocytopenia in the Acutely Ill Patient

Abstract: The numerous drugs to which the acutely ill are exposed place these patients at a significant risk of developing drug-induced thrombocytopenia. Such patients tend to have preexisting hemostatic defects that place them at additional risk of complications as a result of the drug-induced thrombocytopenia. The clinical challenge is to provide rapid identification and removal of the offending agent before clinically significant bleeding or, in the case of heparin, thrombosis results. Drug-induced thrombocytopenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 88 publications
0
37
0
4
Order By: Relevance
“…Non-immune thrombocytopenia caused by drugs results from a loss of cellularity within the bone marrow and an impairment of megakaryocyte proliferation and maturation, thereby leading to a decrease in platelet production. The myelosuppression is dose-dependent and often occurs slowly over the course of several weeks [6]. Chemotherapeutic compounds, including antimetabolites, cytotoxic agents, and alkylating agents are directly toxic to hematopoietic cells.…”
Section: Non-immune Suppression Of Platelet Productionmentioning
confidence: 99%
“…Non-immune thrombocytopenia caused by drugs results from a loss of cellularity within the bone marrow and an impairment of megakaryocyte proliferation and maturation, thereby leading to a decrease in platelet production. The myelosuppression is dose-dependent and often occurs slowly over the course of several weeks [6]. Chemotherapeutic compounds, including antimetabolites, cytotoxic agents, and alkylating agents are directly toxic to hematopoietic cells.…”
Section: Non-immune Suppression Of Platelet Productionmentioning
confidence: 99%
“…The evaluated clinically defined reduced platelet counts included three clinically relevant cutoffs: Յ100,000 cells/mm 3 , Յ50,000 cells/mm 3 , and Յ20,000 cells/mm 3 . These absolute platelet thresholds were evaluated because they, particularly the latter two, have been implicated as carrying an increased risk for spontaneous bleeding (14)(15)(16)(17)(18). In addition, decreases of Յ50% from baseline in patients with normal baseline platelet counts were evaluated because the occurrence of this endpoint has been identified as a meaningful exposure-response reducedplatelet-count outcome (19)(20)(21).…”
Section: Phase 3 Absssi Clinical Trials Establish-1 and Establish-2mentioning
confidence: 99%
“…In addition, a variety of studies have shown that the immunologic activity of the drugs is specifically due to their single active pharmacologic components; in fact, cross-reactivity is absent even between thrombocytopenic drugs, such as quinidine and sulfamethoxazole. 11,12,15 The latter is one of the most frequent drug implicated in thrombocytopenia; it belongs to the class of sulfonamides, which also include sulpha-drugs. 16 The chemical structure of these compounds contains a group constituted by an atom of sulfur with valence 6 and double oxidation (S-O 2 ) and a link with an amino-nitrogen atom (NH 2 ); their general formula is R-SO 2 -NH 2 , with R representing an aromatic group.…”
Section: Discussionmentioning
confidence: 99%